IMPROVING THE STUDENTS` ABILITY AT WRITING DESCRIPTIVE TEXTS BY USING THE LEARNING CELL LEARNING STRATEGY AT GRADE X- FASHION STUDY PROGRAM AT SMK N 2 KOTANOPAN - Dina Syarifah Nasution (Bajang Institute, 2021)
This research aims to measure the implementation of the learning cell learning strategy on improving students` ability at writing descriptive texts of grade x- fashion study program at SMK N 2 Kotanopan , Mandailing Natal-Sumatera Utara. The method of this research was classroom action research. The participants in this classroom action research were 21 students of grade x- fashion study program SMK N 2 Kotanopan. The instrument consisted of the learning cell learning strategy, writing test, observation sheet, and interviews. The data of this research was analyzed two methods of data analysis.Quantitative data analysis was used to examining and interpreting data from the learning cell learning strategy and writing test.The data taken from observation and interview was used qualitative data analysis.the result shows that the learning cell learning strategy better improves the students` ability at writing descriptive texts. This can be evidence from the students` mean which improved gradually in the first cycle and second cycle that there was significance value on students` marks at writing descriptive texts through the learning cell learning strategy. The mean of pre-test was 61, 04, the mean of post-test in first cycle was 74, 23 and the mean of post-test in second cycle was 82, 80. The percentage of the students score in pre-test who got point up to 75 there were only 2 of 21 students (9,52%), and percentage of the student’s score in the cycle I who got point up 75 there were only 8 of 21 students (38,09%). It means that there was an improvement of about 28,57%. Then the percentage of the student’s score in post-test of the second cycle who got a point up 75 there were 19 of 21 students (90,47%). It meant the improvement was 80,95% from the pretest.